Characterising nuclear decommissioning projects: an investigation of the project characteristics that affect the project performance. Issue 10 (2nd October 2020) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Brookes, Naomi J.
Abstract: Historically, project management research on infrastructure has mostly focused on its planning, design and construction. However, globally, more and more infrastructure, such as nuclear power plants, bridges, dams or oil rigs, are reaching their end-of-life and will soon need to be decommissioned. Decommissioning projects are long, complex and range from small projects to multi-billion megaprojects. Their costs keep increasing, while there is a limited understanding of why this happens. Nuclear Decommissioning Projects and Programmes (NDPs) are the unit of analysis of this article, due to the relevance of this sector and the number of public information available. The aim is to identify the NDP characteristics that mostly affect the NDP performance in terms of cost and time. Findings from the application of content analysis on the information collected through 35 interviews with senior practitioners highlight the importance of several NDP characteristics, including the need to have detailed knowledge of the site conditions, a good relationship with the regulatory authorities, the availability of storage facilities and stable funding.